The impact of the european union fiscal rules on economic growth - Castro, Vítor (2007)
This study intends to provide an empirical answer to the question of whether Maastricht and SGP fiscal rules have affected growth of European Union countries. A growth equation augmented with fiscal variables and controlling for the period in which fiscal rules were implemented in Europe is estimated over a panel of 15 EU countries (and 8 OECD countries) for the period 1970-2005 with the purpose of answering this question. The equation is estimated using both a dynamic fixed effects estimator and a recently developed pooled mean group estimator. GMM estimators are also used in a robustness analysis. Empirical results show that growth of real GDP per capita in the EU was not negatively affected in the period after Maastricht. This is the case when the recent performance of EU countries is compared both with their past performance and with the performance of other developed countries. Results even show that growth is slightly higher in the period in which the fulfilment of the 3% criteria for the deficit started to be officially assessed. Therefore, this study concludes that the institutional changes that occurred in Europe after 1992, especially the implementation of Maastricht and Stability and Growth Pact fiscal rules, should not be blamed for being harmful to growth in Europe.